Epidemiology of Extended-Spectrum β-Lactamase-Producing E. coli and Vancomycin-Resistant Enterococci in the Northern Dutch–German Cross-Border Region - Zhou, Xuewei; García-Cobos, Silvia; Ruijs, Gijs J. H. M.; Kampinga, Greetje A.; Arends, Jan P.; Borst, Dirk M.; Möller, Lieke V.; Holman, Nicole D.; Schuurs, Theo A.; Bruijnesteijn van Coppenraet, Lesla E.; Weel, Jan F.; van Zeijl, Jan H.; et al. (Frontiers in Microbiology, 2017)
Objectives; To reveal the prevalence and epidemiology of Extended spectrum β-lactamase (ESBL)- and/or plasmid AmpC (pAmpC)- and carbapenemase (CP) producing Enterobacteriaceae and vancomycin resistant enterococci (VRE) across the Northern Dutch-German border region. Methods; A point-prevalence study on ESBL/pAmpC,/CP producing Enterobacteriaceae and VRE was carried out in hospitalized patients in the Northern Netherlands (n=445, 2012-2013) and Germany (n=242, 2012). Healthy individuals from the Dutch community (n=400, 2010-2012) were also screened. In addition, a genome-wide gene-by-gene approach was applied to study the epidemiology of ESBL-E. coli and VRE. Results; A total of 34 isolates from 27 patients (6.1%) admitted to Dutch hospitals were ESBL/pAmpC positive and 29 ESBL-E. coli, three pAmpC-E. coli, one ESBL-E. cloacae and one pAmpC-P. mirabilis were found. In the German hospital, 18 isolates (16 E. coli and 2 K. pneumoniae) from 17 patients (7.7%) were ESBL positive. In isolates from the hospitalized patients CTX-M-15 was the most frequently detected ESBL-gene. In the Dutch community, 11 individuals (2.75%) were ESBL/pAmpC positive: 10 ESBL E. coli, (CTX-M-1 being the most prevalent gene) and one pAmpC E. coli. Six Dutch (1.3%) and four German (3.9%) hospitalized patients were colonized with VRE. Genetic relatedness by core genome multi-locus sequence typing (cgMLST) was found between two ESBL- E. coli isolates from Dutch and German cross-border hospitals and between VRE isolates from different hospitals within the same region. Conclusions; The prevalence of ESBL/pAmpC-Enterobacteriaceae was similar in hospitalized patients across the Dutch-German border region, whereas VRE prevalence was slightly higher on the German side. The overall prevalence of the studied pathogens was lower in the community than in hospitals in the Northern Netherlands. Cross-border transmission of ESBL-E. coli and VRE seems unlikely based on cgMLST analysis, though continuous monitoring is necessary to keep the epidemiology of resistant pathogens updated thereby helping to control their spread.